Lipoprotein(a) and the atherosclerotic burden – Should we wait for clinical trial evidence before taking action? - Isabella Fichtner; Chiara Macchi; Alessandra Stefania Rizzuto; Stefano Carugo; Alberto Corsini; Massimiliano Ruscica (Atherosclerosis Plus)
The fact that lipoprotein(a) levels should be regarded as a causal residual risk factor in the atherosclerotic cardiovascular diseases (ASCVD) is now a no-brainer. This review article aims to summarize the latest evidence supporting the causal role of lipoprotein(a) in ASCVD and the potential strategies to reduce the lipoprotein(a) burden until clinical trial results are available. Epidemiological and genetic data demonstrate the causal link between lipoprotein(a) and increased ASCVD risk. That being said, a specific question comes to mind: “must we wait for outcome trials in order to take action?”. Given that lipoprotein(a) levels predict incident ASCVD in both primary and secondary prevention contexts, with a linear risk gradient across its distribution, measuring lipoprotein(a) can unequivocally help identify patients who may later benefit from specific lipoprotein(a)-lowering therapies. This understanding has led various National Societies to recommend dosing lipoprotein(a) in high-risk individuals and to support the recommendation of measuring lipoprotein(a) levels at least once in every adult for risk stratification.